Exploring Strategy In Teaching Vocabulary (Qualitative Case Study Of Member Quarantine And TOT Program of Libam IAIN Parepare) - Arif, Hadi (Al-Iftah: Journal of Islamic studies and society, 2023)
This research was carry out at LIBAM IAIN Parepare. Problem in this research is that the strategy used by instructors in the Quarantine and TOT program by LIBAM IAIN Parepare has not been revealed in increasing the vocabulary of the participants. This study aims to describe the strategies used by activity of instructors in increasing vocabulary in the program. This type of research is qualitative research. The research subjects were instructors and participants in the Quarantine and TOT by LIBAM IAIN Parepare, totaling 22 people. The sampling technique was carried out by the snowball sampling method. The key instrument in this research is the researcher himself. The data collection technique chosen by the researcher is interview. To test the validity of the data, the researcher conducted Source Triangulation between the instructors and the participants. Data analysis techniques were carried out by referring to Miles and Huberman, namely data reduction, data display and data conclusion. The results of the research showed that the strategy used by the instructors in increasing the vocabulary of Quarantine and TOT by LIBAM IAIN Parepare was presentation strategies (using of picture, using body movement (gesture), using video, translation and exemplification), practice strategy (classroom test and games), strategy for strategies training (guessing from context and looking up dictionaries).